1987
DOI: 10.1128/mcb.7.2.951
|View full text |Cite
|
Sign up to set email alerts
|

A 5'-flanking region of the chicken acetylcholine receptor alpha-subunit gene confers tissue specificity and developmental control of expression in transfected cells.

Abstract: The 5' end and promoter region of the a-subunit gene of chicken muscle acetylcholine receptor was mapped and sequenced. It includes a TATA and a CAAT box and a potential Spl-binding site. When inserted in front of the chloramphenicol acetyltransferase gene, this promoter (including 850 base pairs of upstream sequence) directed high transient chloramphenicol acetyltransferase expression in transfected mouse C2.7 myotubes but not in C2.7 myoblasts or nonmyogenic 3T6 cells.The genes encoding the nicotinic acetylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 33 publications
1
59
0
Order By: Relevance
“…Rather, the CHX experiments reported here suggest that synthesis of an activator protein precedes the denervation-triggered receptor up-regulation. This agrees with the identification, in the promoter regions of the chick AChR ct- [16][17][18] Nuclease protection analysis was performed as described in Materials and Methods, with 30 p.g of total RNA and an excess of 10-fold or greater of radiolabeled riboprobe. Lane 1: intact ct-subunit probe; 2: molecular weight markers (¢~X174/HaelII); 3" CHX (at 0.2 mg/kg body weight) administered i.p.…”
Section: Chx Blocks Denervation-induced Rise In A-subunitsupporting
confidence: 79%
“…Rather, the CHX experiments reported here suggest that synthesis of an activator protein precedes the denervation-triggered receptor up-regulation. This agrees with the identification, in the promoter regions of the chick AChR ct- [16][17][18] Nuclease protection analysis was performed as described in Materials and Methods, with 30 p.g of total RNA and an excess of 10-fold or greater of radiolabeled riboprobe. Lane 1: intact ct-subunit probe; 2: molecular weight markers (¢~X174/HaelII); 3" CHX (at 0.2 mg/kg body weight) administered i.p.…”
Section: Chx Blocks Denervation-induced Rise In A-subunitsupporting
confidence: 79%
“…12). The region between -1242 and -1232 shares 80% homology with a 10-bp element upstream of the chicken ACh receptor asubunit gene (29). An 8-bp segment of this sequence from the ACh receptor upstream region is repeated three times in the MCK proximal region, where it overlaps with three 17-bp imperfect repeats that were identified previously (28) to be associated with other muscle-specific genes (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of such homology suggests a strong evolutionary constraint on these sequences and has led to speculation concerning their potential involvement in muscle-specific regulation. Transfection studies of muscle cells in tissue culture also have demonstrated sequences adjacent to or within the genes encoding skeletal cx actin (3,18,35,45), cardiac a actin (23,37,38), the ACh receptor a subunit (29), MCK (28), Tn-I (30,31), MHC (6), and MLC type 2 (MLC-2) (43) that are sufficient to direct differentiation-specific expression. Sequences upstream from a subset of these genes also have been shown to direct appropriate expression in transgenic mice (60,61), Xenopus oocytes (63), and Drosophila melanogaster (15).…”
mentioning
confidence: 99%
“…2A). ␣1KK encompasses nucleotides 151-334 of the chick ␣1 nAChR promoter (19,20) (GenBank TM accession number M15307), flanked by KpnI restriction sites that were used for subcloning into pCAT00. The ␣1/␤3 hybrid promoter was obtained by ligation of the 5Ј-end of ␣1KK with the 3Ј-end of ␤3RS at their shared PvuII restriction site (Fig.…”
Section: Methodsmentioning
confidence: 99%